2020
DOI: 10.22492/ije.8.4.07
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Praxis: Muslim-Filipino Madrasah Teachers’ Conceptuality of Instructional Process

Abstract: The purpose of this paper is to explore and analyze the conceptuality of Muslim-Filipino Madrasah teachers or the Asatidz on instructional processes anchored in their pedagogical praxis. This study employed a qualitative research design using a transcendental phenomenological approach. In-depth interviews were initiated to understand the essence of the participants’ lived experiences. The author used purposive sampling with five research participants who implement the Arabic Language and Islamic Values Educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Despite their situations, navigating their way to teaching-learning processes is tolerable because of their divine solitude towards their profession. Sali (2020) underscores that they view their role as a divine responsibility, transcending the conventional concept of a job. In the current study, it became evident that the participants strongly believed that knowledgeable Muslims have a sacred duty to disseminate their Islamic wisdom to the wider Muslim community.…”
Section: Religious Obligationsmentioning
confidence: 99%
“…Despite their situations, navigating their way to teaching-learning processes is tolerable because of their divine solitude towards their profession. Sali (2020) underscores that they view their role as a divine responsibility, transcending the conventional concept of a job. In the current study, it became evident that the participants strongly believed that knowledgeable Muslims have a sacred duty to disseminate their Islamic wisdom to the wider Muslim community.…”
Section: Religious Obligationsmentioning
confidence: 99%
“…According to the analysis results, incorporating life skills education and anchoring 'caring' as the core value of the nursing profession becomes a vital component, for instance, in developing a holistic curriculum. Therefore, the striking balance of cognitive, psychomotor, and emotional prowess is unprecedented (Sali, 2020b). Consequently, Pryjmachuk and Richards (2007) found that stress in nursing students arises from personal and extracurricular factors.…”
Section: Caring As a Core Valuementioning
confidence: 99%
“…However, it was noted that the Asatidz had high dependency on textbooks and didactic in inculcating values formation (Muslim Education Initiative Review Final Report, 2014). Furthermore, despite showing diversity in teaching practices and pedagogical praxis (Sali, 2020a) based on the actual classroom observation, a significant number of the Asatidz showed disconnect between the lesson objective and the formative assessment chosen for evaluation. Considerably, a significant number of madrasah teachers hired to implement the ALIVE program were high school graduates in secular education.…”
Section: On Madrasah Education Curriculum Of Alive Programmentioning
confidence: 99%
“…At present, madrasah teaches Islamic knowledge and is distinct in the context of architecture, organisation, instruction, learning, curriculum and funding sources (Kadi, 2006, as cited in Sabki & Hardarker, 2013. The madrasah education implementation (Arsad, 2007;Boransing, 2006;Marasigan 2019a;Marasigan 2019b;Milligan, 2006;Rodriguez, 1986;Sali, 2020a;Sali, 2020b;Sali & Ancho, 2021;Sali & Marasigan, 2020;Solaiman, 2017) in the Philippines is multifaceted. The institutionalisation of Arabic Language and Islamic Values Education (ALIVE) program was made possible through a series of consultations and efforts of the government and Muslim intellectuals (Sali & Marasigan, 2020, p. 204).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation